Fabaceae - Chalup, Laura María Isabel (2013)
In the present study 19 populations belonging to 8 species of the genus Lathyrus L. were examined cytologically. Seven of these species belong to the South American section, Notolathyrus and other species is included in the section Lathyrus. All species analyzed were diploids with 2n = 2x= 14. These results include the first chromosome number reports for L. nitens Burk. and L. magellanicus var. glauscecens. The chromosome numbers of the remaining species agree with those published previously.